1987
DOI: 10.1039/c39870000279
|View full text |Cite
|
Sign up to set email alerts
|

Host–guest complex formation by a solid–solid reaction

Abstract: Some host-guest complexes have been formed by mixing the components in the solid state, and complexation has been shown to proceed with some selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
0
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(105 citation statements)
references
References 2 publications
0
102
0
2
Order By: Relevance
“…Pioneering studies were carried out by Toda et al in the preparation of crystalline host-guest inclusion compounds [152] and charge-transfer systems. [153] Formation of charge transfer cocrystals can often be followed by eye due to the change in color.…”
Section: Charge Transfer Cocrystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pioneering studies were carried out by Toda et al in the preparation of crystalline host-guest inclusion compounds [152] and charge-transfer systems. [153] Formation of charge transfer cocrystals can often be followed by eye due to the change in color.…”
Section: Charge Transfer Cocrystalsmentioning
confidence: 99%
“…perhaps employed only when there was no solvent-based alternative. Molecular mechanochemistry, particularly cocrystallization, developed significantly in the 1980s and 90s (Curtin, Paul, [11] Toda, [12] Etter, [13] Jones, [14] Hollingsworth [15] and Caira [16] ). These studies showed that mechanochemistry was not only a general way to make cocrystals, but also that it could give products not obtainable by solution-based methods.…”
Section: A Brief Historymentioning
confidence: 99%
“…In our previous studies on the intercalation of polar molecules into montmorillonites by solid-solid reactions (Ogawa et al, 1989(Ogawa et al, , 1990a(Ogawa et al, , 1991, we have found that the reactions were completed within a few minutes. Toda et al (1987) mentioned that some organic host-guest complexes formed faster in the solid-state than in solutions. Since the solid-solid reactions are conducted with high concentration, it is possible that the reactions proceed very fast.…”
Section: Intercalation Of Naphthalene Into Alkylammonium-rnontmorillomentioning
confidence: 99%
“…The pioneering work of Toda et al 8 has shown that many exothermic reactions can be accomplished in high yield by just grinding solids together using mortar and pestle, a technique known as 'Grindstone Chemistry' which is one of the 'Green Chemistry Techniques'. Reactions are initiated by grinding, with the transfer of very small amounts of energy through friction 9 .…”
Section: Introductionmentioning
confidence: 99%